2020
DOI: 10.1177/1078155220943964
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacy in onco-hematology and bone marrow transplant: A valuable contribution to improving patient safety

Abstract: Introduction It is known that clinical pharmacists intercept prescribing errors and contribute to patient safety in several medical specialties. The aim of this study was to identify, quantify and classify prescribing errors and pharmacist interventions carried out in onco-hematology and bone marrow transplant inpatient units. Methods This was a prospective and quantitative study, conducted from February 2018 to July 2018 in onco-hematology and bone marrow transplant inpatient units of a tertiary teaching hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…The interventions identified in this study are not unique to the clinical trial realm, as similar types of patient safety interventions are common practices within standard of care, particularly within the oncology pharmacy domain 18,19 . While standard of care interventions are well documented, to our knowledge, this is the first study to highlight interventions identified during EHR clinical content development to potentially prevent patient harm.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The interventions identified in this study are not unique to the clinical trial realm, as similar types of patient safety interventions are common practices within standard of care, particularly within the oncology pharmacy domain 18,19 . While standard of care interventions are well documented, to our knowledge, this is the first study to highlight interventions identified during EHR clinical content development to potentially prevent patient harm.…”
Section: Discussionmentioning
confidence: 98%
“…The interventions identified in this study are not unique to the clinical trial realm, as similar types of patient safety interventions are common practices within standard of care, particularly within the oncology pharmacy domain. 18,19 While standard of care interventions are well documented, to our knowledge, this is the first study to highlight interventions identified during EHR clinical content development to potentially prevent patient harm. Dedicating a team of centralized clinical specialists to review and translate clinical trial documents for implementation is one method of establishing best practice institutional guidelines for enhancing patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…After having highlighted the role of the clinical pharmacist in specific fields such as onco-hematology and bone marrow transplant, 29 pediatric hematology-oncology, 30 and providing patient counselling for patients with gastrointestinal cancer receiving oral anticancer treatment (capecitabine), 31 we discussed another specific field in this paper which is palliative care for patients with cancer. This scoping review identified 14 relevant studies on the activities and-or services provided by clinical pharmacists in the palliative care of adults and elderly patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Potential drug-drug interactions (DDIs) are particularly common among HSCT patients in the bone marrow transplantation unit (1) . The identification and resolution of drug-related problems (DRP) constitute a very important role of the clinical pharmacist in managing drug therapy, and several general guidelines and recommendations have been provided to define the role of hospital pharmacists in caring for HSCT patients (2)(3)(4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%